Features of symptoms, diagnosis and treatment of inflammatory bowel diseases in elderly patients - L. V. Tarasova; N. Y. Kucherova; T. E. Stepashina (Лечащий Врач)
Currently, there has been an increase in cases of inflammatory bowel disease with a late onset in elderly patients, which makes it urgent to study the pathogenesis, clinical features, diagnosis and treatment of inflammatory bowel disease in this age group. Up to 35% of inflammatory bowel disease cases are first diagnosed in patients over 60 years of age. In this category of patients low-manifest forms of inflammatory bowel disease are observed more often than others with a more frequent occurrence of extraintestinal manifestations. Genetics contribute less to the pathogenesis of inflammatory bowel disease and age-related changes (dysbacteriosis, impaired intestinal barrier function, dysregulation of the immune system and regeneration mechanisms) play a more significant role. Ulcerative colitis is more common in older adults. Asymptomatic forms prevail with a relatively stable course. When treating elderly patients the development of geriatric syndromes, multimorbidity, polypharmacy should be taken into account. Particular attention should be paid to the safety of therapy, while maintaining maximum adherence to treatment. Careless prescribing of glucocorticosteroids should be avoided, and if indicated, more often resort to steroid-sparing regimens, especially with the use of 5-aminosalicylic acid preparations, should be used. A prolonged form of mesalazine in the form of microgranules with a semipermeable membrane of ethyl cellulose has a pronounced clinical advantage with a minimal frequency of side effects among this group. When inducing remission in elderly patients with mild to moderate active ulcerative colitis topical glucocorticosteroids may be considered. The advantages of continuing therapy with 5-aminosalicylic acid preparations against the background of the use of genetically engineered biological preparations, thiopurines require further reflection. The risk of surgery in older patients with inflammatory bowel disease is comparable to that of inflammatory bowel disease onset at a young age and does not result in increased surgical morbidity or mortality compared with a younger cohort in the delayed postoperative period.